Integrating Reading-Based Needs Analysis Into Syllabus Design And Material Development In English Language Education - Rahma Dania; Fitrawati; Yetti Zainil (Jurnal Ilmiah Langue and Parole, 2026)
Reading plays a central role in English language education, particularly in higher education contexts where learners are required to engage with complex academic texts. Despite its importance, reading instruction is often designed without sufficient consideration of learners’ actual reading needs, resulting in misalignment between instructional objectives, materials, and students’ academic demands. This study aims to explore how reading-based needs analysis can be integrated into syllabus design and material development in English language education. Employing a qualitative, curriculum-oriented research design, the study analyzes curriculum documents, instructional materials, and reading-related learning practices within an undergraduate English language education program. Data were derived from document analysis, classroom observations, students’ reading-related tasks, questionnaires, and reflective records. The findings indicate that students initially experienced difficulties in understanding academic texts, applying reading strategies effectively, and engaging confidently in reading activities. After the integration of reading-based needs analysis into syllabus design and material development, improvements were observed in students’ reading engagement, comprehension processes, strategy use, and attitudes toward academic reading. The revised syllabus emphasized progressive reading skills, while the developed materials incorporated structured reading stages, explicit strategy instruction, and discipline-related texts. These findings suggest that reading-based needs analysis serves as a crucial foundation for developing responsive syllabi and effective instructional materials that address learners’ academic reading demands. The study highlights the importance of positioning needs analysis as an ongoing pedagogical framework in reading-oriented curriculum development.